Design Of Power Cycling Test Set-up For Power Devices - Alnatshih, Mahmoud; Hries, Mekawi; Edkaidek, Mohammad (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2008)
in this project a power cycling test set up has been designede . the power cycling test is used for life time prediction of power devices. .......
no of pages 51 , 23723 , ميكانيك 3/2008 , in the store
Keywords: Power Devices